Decavanadate binding to a high affinity site near the myosin catalytic centre inhibits F-actin-stimulated myosin ATPase activity - Tiago, Teresa (2012)
Decameric vanadate (V10) inhibits the actin-stimulated myosin ATPase activity, noncompetitively with actin or with ATP upon interaction with a high-affinity binding site (Ki ) 0.27 ( 0.05 íM) in myosin subfragment-1 (S1). The binding of V10 to S1 can be monitored from titration with V10 of the fluorescence of S1 labeled at Cys-707 and Cys-697 with N-iodo-acetyl-N¢-(5-sulfo-1-naphthyl)- ethylenediamine (IAEDANS) or 5-(iodoacetamido) fluorescein, which showed the presence of only one V10 binding site per monomer with a dissociation constant of 0.16-0.7 íM, indicating that S1 labeling with these dyes produced only a small distortion of the V10 binding site. The large quenching of AEDANSlabeled S1 fluorescence produced by V10 indicated that the V10 binding site is close to Cys-697 and 707. Fluorescence studies demonstrated the following: (i) the binding of V10 to S1 is not competitive either with actin or with ADPâV1 or ADPâAlF4; (ii) the affinity of V10 for the complex S1/ADPâV1 and S1/ ADPâAlF4 is 2- and 3-fold lower than for S1; and (iii) it is competitive with the S1 “back door” ligand P1P5-diadenosine pentaphosphate. A local conformational change in S1 upon binding of V10 is supported by (i) a decrease of the efficiency of fluorescence energy transfer between eosin-labeled F-actin and fluorescein-labeled S1, and (ii) slower reassociation between S1 and F-actin after ATP hydrolysis. The results are consistent with binding of V10 to the Walker A motif of ABC ATPases, which in S1 corresponds to conserved regions of the P-loop which form part of the phosphate tube.